2004
DOI: 10.1002/adfm.200305049
|View full text |Cite
|
Sign up to set email alerts
|

Relating the Morphology of Poly(p‐phenylene vinylene)/Methanofullerene Blends to Solar‐Cell Performance

Abstract: The performance of bulk‐heterojunction solar cells based on a phase‐separated mixture of donor and acceptor materials is known to be critically dependent on the morphology of the active layer. Here we use a combination of techniques to resolve the morphology of spin cast films of poly(p‐phenylene vinylene)/methanofullerene blends in three dimensions on a nanometer scale and relate the results to the performance of the corresponding solar cells. Atomic force microscopy (AFM), transmission electron microscopy (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
540
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(576 citation statements)
references
References 40 publications
30
540
0
2
Order By: Relevance
“…24 Janssen and coworkers performed a detailed study of the morphology of MDMO-PPV:PCBM blends with varying PCBM concentration processed from chlorobenzene. 26 No obvious phase separation was observed when the concentration of PCBM was less than 50 wt %. With PCBM concentrations higher than 67 wt %, domains of PCBM began to appear.…”
Section: Morphology Of Polymer Based Opvsmentioning
confidence: 99%
“…24 Janssen and coworkers performed a detailed study of the morphology of MDMO-PPV:PCBM blends with varying PCBM concentration processed from chlorobenzene. 26 No obvious phase separation was observed when the concentration of PCBM was less than 50 wt %. With PCBM concentrations higher than 67 wt %, domains of PCBM began to appear.…”
Section: Morphology Of Polymer Based Opvsmentioning
confidence: 99%
“…P in a , where a < 1 [for dominant bimolecular recombination a ¼ 0.5 (Ref. 13) and for dominant space charge limitation a ¼ 0.75]. 11,12 The values G and a are extracted by:…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, for BHJ OPV it was studied only for C 1 sun. 13,32,33 Ultrasmall bilayer C 60 /copper phthalocyanine (CuPc) cells were characterized up to 12 suns of simulated illumination. 34 Recently, 35 we reported an experimental exploitation of concentrated sunlight for such measurements and demonstrated that the PCE of 1 cm 2 P3HT:PCBM BHJ cells peaks at $ 1 sun.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent efforts have focused on the synthesis of a new low-band gap conjugated polymers that improve the absorption of solar radiation and increase charge mobilities. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] In addition to the intrinsic characteristics of the polymer, the amount of PCBM in the blend, 17,18 the compatibility of the polymer and PCBM, the morphology of the photoactive layer [19][20][21] and the deviceprocessing conditions all have important roles affecting the photovoltaic (PV) performance of PSCs. [8][9][10]22,23 Photo-energy conversion efficiencies (Z) of 47% have been achieved for PSCs based on blends of poly(thiophene) derivatives and fullerene derivatives.…”
Section: Introductionmentioning
confidence: 99%